The State of River Transportation after the Development of Land Transport in East Sumatera 1900-1942 - Edi Sumarno; Nina Karina; Junita Setiana Ginting; Handoko Handoko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The ports’ sites on the river bank were closely related to the river, as the primary and easy means of transportation. Through rivers, the crops from upstream were brought to downstream to be traded and exported abroad, especially to Penang. On the other hand, it was also through the river that the goods were imported from downstream to upstream. In other words, with the absence of land transport, the rivers became very dominant. However, after the presence of plantations, the abundant crops required a more efficient and effective transportation, therefore, the development of land transport, for instance railroad and highway, were paramount. The construction of land transportation facilities certainly had an impact on river transportation. The impact was that river transportation was increasingly abandoned because it was ineffective and inefficient. However, there were several rivers that remained became the most important means of transportation.